Anxiety and depression among infertile women: a cross-sectional survey from Hungary - Lakatos, Enikő; Sexty, Réka E. (BMC women's health, 2017)
Infertility is often associated with a chronic state of stress which may manifest itself in anxiety-related and depressive symptoms. The aim of our study is to assess the psychological state of women with and without fertility problems, and to investigate the background factors of anxiety-related and depressive symptoms in women struggling with infertility.
Gesehen am 25.10.2018